Impacts of EU Grant-Assisted Projects on Institutional Capacity Building and Regional Development in Turkey: The Case of NUTS-2 Region TR82 - HILAL ABACI (Ekonomista, 2021)
Benefiting from European Union financial aid since 1963, Turkey has been receiving financial support as part of the Instrument for Pre-Accession Assistance (IPA II) (2014–2020) available to candidate and potential candidate countries. There were 3 687 EU grant-assisted projects implemented in Turkey under the responsibility of the Central Finance and Contracts Unit (CFCU) until 2016. The total amount of grants for these projects was 452 million € and 381 million € of this amount was EU grant contribution. The aim of this study is to explore the impact of the EU’s financial aid rendered through these projects on the institutional capacity building and regional development. The research area covered by the study is one particular region of the country, namely NUTS-2 region TR82. Primary data was collected through a questionnaire sent to subjects sampled from institutions/organizations, which are located in the region and carried out projects received through the CFCU before 2016. The chi-square (χ2) test was used to test the relationship between the legal status, location (city), project management experience of the institutions/organizations surveyed and the effects related to institutional capacity building and regional development. The results of the analyses are presented and interpreted. Together these analyses show that EU grant-assisted projects implemented through the CFCU contribute to institutional capacity building and regional development.